Pancasila as a Foundation for Legal Reform: Evaluating the Impact of Civic Education on Indonesian Legal Systems - Prakoso, Prakoso; Rokhman, Fathur; Handoyo, Eko (Universitas Negeri Semarang, 2024)
Pancasila, Indonesia’s official state ideology, serves as a guiding framework for the nation’s governance and legal systems. As the country continues to grapple with challenges related to corruption, inequality, and legal inefficiencies, there is an increasing recognition of the need to integrate Pancasila’s principles into legal reforms. This study evaluates the impact of civic education, grounded in Pancasila, on the effectiveness and legitimacy of Indonesia’s legal system. It argues that embedding Pancasila’s values—such as justice, democracy, and social welfare—into civic education can foster a more law-abiding, ethically responsible society, which in turn strengthens the rule of law and enhances legal reforms. Through a comprehensive analysis of existing civic education programs and their influence on public understanding of legal rights and obligations, this research highlights the role of education in shaping legal consciousness and promoting societal trust in legal institutions. The urgency of this research lies in Indonesia’s ongoing efforts to modernize its justice system while addressing systemic corruption and inefficiency. By situating Pancasila at the core of civic education, the study advocates for a holistic approach to legal reform, one that aligns legal practices with broader societal values. This research contributes to the discourse on legal reform by proposing a model in which education, ethical values, and legal practice are interconnected to create a more robust and transparent legal framework in Indonesia.